The Khene: A Lao Mouth Organ of the lsan Region of Thailand - Ahmad Faudzi, Musib; Aaliyawani E., Sinin; Sinin, Hamdan; Khairul Anwar, Mohamad Said; Ezra A., M. Duin (NC State University, 2025)
The khene is a musical instrument from Thailand’s Isan region (the Thai term for Northeastern Thailand and its local Thai inhabitants). The Fast Fourier Transform (FFT) of khene signal was determined via a Pico oscilloscope. Tubes 1, 2, 3, 4, 5, 6, 7, and 8 on the right and left side produced the fundamental frequency (in hertz) as 221(A3 = 220), 255(C4 = 261), 384(G4 = 394), 443(A4 = 440), 499(B4 = 493), 591(D5 = 587), 672(E5 = 659), and 887(A5 = 880) and as 519(C5 = 523), 247(B3 = 247), 293D4(293), 329(E4 = 331), 342(F4 = 349), 395(G4 = 392), 683(F5 = 698), and 781(G5 = 783), respectively. The standard deviations of the fundamental pitch from the equal tempered scale (ETS) for tube 1, 2, 3, 4, 5, 6, 7, and 8 on the right and left side were ± 1, ± 6, ± 10, ± 3, ± 6, ± 4, ± 13, ± 7 and ± 4, ± 0, ± 0, ± 2, ± 7, ± 3, ± 15, ± 2 Hz, respectively. The tunings were remarkably similar with the diatonic scale of ETS. The linear equation for the partial frequency versus harmonic number for tube 1 to 8 from the right and the left side is given by y1 = 220x + 1.31, y2 = 255x + 0.34, y3 = 384x + 0.77, y4 = 443x + 0.19, y5 = 499x – 0.13, y6 = 591x + 1.82, y7 = 672.x + 2.35, and y8 = 887x, and y1 = 519x + 0.14, y2 = 247x – 0.07, y3 = 293x + 0.40, y4 = 331x – 5.49, y5 = 341x + 1.70, y6 = 395x + 0.38, y7 = 683x – 0.4, and y8 = 782x – 0.50, respectively. The harmonic number of tubes 1 to 8 on the right and left side were 16, 14, 9, 8, 7, 6, 5, 7, and 7, 14, 10, 10, 11, 9, 5, 4, respectively.